Experimental investigation of phase equilibria in the Fe-Hf-Zr system at 1173 K and 1373 K. (March 2021) - Zou, Nan; Lu, Hai-Jin; Liu, Li-Li; He, Yan-Lin; Lu, Xiao-Gang
Abstract: A series of Fe-Hf-Zr alloys were designed to determine the phase equilibria for the entire composition range by annealing at 1173 K and 1373 K for 440–720 h and 12–360 h respectively, followed by X-ray diffraction (XRD) measurements and electron probe microanalysis (EPMA). At the Fe-rich corner, it was argued that the Fe23 Zr6 phase is a stable phase without oxygen contamination, of which the formation mechanism was discussed. The Fe2 (Hf, Zr)_C15 phase forms a continuous solid solution. The two-phase region of β(Hf, Zr) + Fe(Hf, Zr)3 was detected at 1173 K. The Fe(Hf, Zr)3 phase was observed in this ternary system at 1173 K, which is attributed to the increasing thermodynamic stability by dissolving Hf. The solubility of Fe in α(Hf, Zr) was determined to be extremely low. The liquid phase appears at 1373 K in a large composition range. No ternary compound was identified at both temperatures in this system. Based on the experimental results and reasonable extrapolations, the isothermal sections of 1173 K and 1373 K were constructed, which respectively consist of seven and five three-phase regions. Highlights: Isothermal sections at 1173 K and 1373 K of the Fe-Hf-Zr system were determined. The Fe23 Zr6 phase was confirmed to exist without the oxygen contamination. The dissolving of Hf increases the thermodynamic stability of the Fe(Hf, Zr)3 phase. The liquid phase shows a wide homogeneity range at 1373 K. No ternary compound was detected on these isothermal sections.